Algorithms for noise reduction in signals : theory and practical examples based on statistical and convolutional analysis - Iglesias Martínez, Miguel Enrique; García March, Miguel Ángel; Milián Enrique, Carles; Fernández de Córdoba, Pedro (IOP (Series). Release 22., 2022)
This book is the result of an exhaustive review of the general algorithms used for noise reduction using two general application criteria: one-input, one-output systems, and two-input, one-output systems.